2002
DOI: 10.1140/epjc/s2002-01034-1
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical symmetry breaking in SYM theories as a non-semiclassical effect

Abstract: We study supersymmetry breaking effects in N = 1 SYM from the point of view of quantum effective actions. Restrictions on the geometry of the effective potential from superspace are known to be problematic in quantum effective actions, where explicit supersymmetry breaking can and must be studied. On the other hand the true ground state can be determined from this effective action, only. We study whether some parts of superspace geometry are still relevant for the effective potential and discuss whether the gr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 79 publications
(144 reference statements)
0
2
0
Order By: Relevance
“…All possible gauge transformations can be expressed as a linear combination of these two [23]. Two equations, either (10) or (11), are sufficient to determine the gauge transformation of all the CDG components of the gluon field because they can all be expressed in terms of A μ and the ni by…”
Section: Restricting the Gauge Degrees Of Freedommentioning
confidence: 99%
See 1 more Smart Citation
“…All possible gauge transformations can be expressed as a linear combination of these two [23]. Two equations, either (10) or (11), are sufficient to determine the gauge transformation of all the CDG components of the gluon field because they can all be expressed in terms of A μ and the ni by…”
Section: Restricting the Gauge Degrees Of Freedommentioning
confidence: 99%
“…Another study [8] found that SUSY was broken in SQCD when the number of flavours was less than the number of colours. A later study of the thermodynamic limits of SQCD [9] found that confinement implies SUSY breaking, and another [10] makes a careful study of the superspace geometry to conclude that SUSY is dynamically broken by non-semiclassical effects that transform auxiliary fields into dynamic ones. (This summary is by no means definitive and readers are also directed to the references within these citations, and to reviews such as [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%